Does exchange rate risks matter for exports? a case of Malaysia - Mohd. Sidek, Noor Zahirah; Yusoff, Mohammed; Duasa, Jarita; Mat Ghani, Gairuzazmi (UPENA, UiTM., 2010)
This paper attempts to estimate the impact of exchange rate risks on exports using Pesaran et al. (2001) bounds testing procedure to establish cointegration. The long run coefficients are estimated via the autoregressive distributed lag (ARDL) model. Results suggest that exchange rate risks depress exports in the long run with the impact of exchange rate misalignment being stronger than exchange rate volatility.